Clinical assessment of hepatic de novo lipogenesis in non-alcoholic fatty liver disease. Issue 1 (December 2016) - Paglialunga, Sabina; Dehn, Clayton
Abstract Non-alcoholic fatty liver disease (NAFLD) is heralded as the next big global epidemic. Hepaticde novo lipogenesis (DNL), the synthesis of new fatty acids from non-lipid sources, is thought to play a pivotal role in the development of NAFLD. While there is currently no NAFLD-specific therapeutic agent available, pharmaceutical drugs aimed at reducing hepatic fat accretion may prove to be a powerful ally in the treatment and management of this disease. With a focus on NAFLD, the present review summarizes current techniques examining DNL from a clinical perspective, and describes the merits and limitations of three commonly used assays; stable-label isotope tracer studies, fatty acid indexes and indirect calorimetry as non-invasive measures of hepatic DNL. Finally, the application of DNL assessments in the pharmacological and nutraceutical treatment of NAFLD/NASH is summarized. In a clinical research setting, measures of DNL are an important marker in the development of anti-NAFLD treatments.